2017
DOI: 10.1097/qai.0000000000001510
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Efavirenz as Initial Antiretroviral Therapy and Suicidal Thoughts Among HIV-Infected Adults in Routine Care

Abstract: Background Evidence about the effect of initiating efavirenz-containing combination antiretroviral therapy (ART) as first-line therapy on suicidal thoughts remains conflicting. Methods Using data from a cohort of HIV-infected adults enrolled in routine care across 5 sites in the United States, we included participants with a baseline patient-reported outcome measure and detectable viral load who initiated ART between 2011 and 2014. Participants were followed until the earliest of the following: first suicida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…Finally, this study reports associations that do not imply causality. Despite these limitations, a strength of the present study compared to previous studies was the assessment of efavirenz by DBS (39). …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Finally, this study reports associations that do not imply causality. Despite these limitations, a strength of the present study compared to previous studies was the assessment of efavirenz by DBS (39). …”
Section: Discussionmentioning
confidence: 92%
“…A recent study (10) has suggested that the impact of efavirenz on suicidal ideation is neither clinically relevant nor time limited, finding “no strong evidence” that self-reported initiation of efavirenz-containing ARV regimens increased suicidal thoughts. However, using DBS drug levels, the current study found that detectable efavirenz at 32-weeks predicted suicidal ideation at 12-months post-partum (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other psychiatric reactions such as hallucinations, depression and suicidal ideation were not reported by our children, but are recognized more in adults and adolescents. 24,25 Long-term manifestations included poor working memory, attention span, verbal comprehension, perceptual reasoning, processing speed and visuospatial skills, as well as poor executive functioning and borderline to extremely low IQ (ranging from 48 to 70), all of which can lead to poor academic performance. Poor neurocognitive outcomes following long-term efavirenz use, particularly decreased verbal fluency, working memory and processing speed, are reported in adults.…”
Section: Discussionmentioning
confidence: 99%
“…This caution is not only useful in South Africa, but also in other parts of sub-Saharan Africa where the CYP2B6 G>T polymorphism is widely expressed [25][26][27][28][29]. As in South Africa, routine drug monitoring and genetic testing are not available in these countries.…”
Section: Introductionmentioning
confidence: 99%